2018
DOI: 10.2147/opth.s150816
|View full text |Cite
|
Sign up to set email alerts
|

Glaucoma therapy: preservative-free for all?

Abstract: Preservatives used in topical glaucoma medications have a plethora of well-described toxic effects on the ocular surface. Such ocular toxicity is manifest clinically as ocular surface disease (OSD) and has been confirmed in epidemiologic, prospective clinical trials and studies in which patients are switched from preservative-added to preservative-free topical therapy. Such toxicity has implications not only for tolerability, but also for adherence and persistence with therapy that is known to be poor in glauc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0
10

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(51 citation statements)
references
References 88 publications
0
37
0
10
Order By: Relevance
“…Furthermore, it appreciating the fact that a prolonged use of preserved glaucoma eye drops causes OSDs as well as other ocular signs and symptoms while they do not provide any better clinical efficacy than PF latanoprost eye drops, thus supporting the clinical relevance of the findings in this study. 26 …”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it appreciating the fact that a prolonged use of preserved glaucoma eye drops causes OSDs as well as other ocular signs and symptoms while they do not provide any better clinical efficacy than PF latanoprost eye drops, thus supporting the clinical relevance of the findings in this study. 26 …”
Section: Discussionmentioning
confidence: 99%
“…In addition, a consensus on how to define success is needed. ocular surface [19]. Kim [20] showed that glaucoma patient using topical medications had a higher incidence of Meibomian gland disease than controls.…”
Section: Key Pointsmentioning
confidence: 99%
“…Ряд авторов указывают на существенное повышение приверженности у пациентов, получающих бесконсервантную терапию. Бесконсервантные препараты ни в чем не уступают консервантным формам, а с позиций качества жизни, приверженности к лечению, улучшения прогноза последующего хирургического лечения превосходят их для всех категорий пациентов [15]. Тем не менее доля бесконсервантных препаратов в терапии глаукомы по-прежнему остается небольшой.…”
Section: Influence Of Treatment Adherence On the Progression Of Primaunclassified